Developing assemblr edu to improve elementary school students’ explanatory text writing - Sartika Ayu; Arum Fatayan (University of Muhammadiyah Malang, 2024)
All Indonesians normally master Bahasa Indonesia (BI), but Indonesia’s elementary school students’ learning outcomes for writing explanatory texts in BI are low. This research aims to develop the feasibility of Assemblr Edu in improving students’ ability to write explanatory texts in BI for fifth graders. The research and development (R&D) method with the ADDIE approach was employed. The participants were 30 fifth graders who underwent trial, and series of data collection including observation, interviews, questionnaires, and documentation. The obtained data were analysed quantitatively and qualitatively. The results show that Assemblr Edu is suitable for development at 95% per cent feasibility. The media was also proven to improve students’ ability to write explanatory text.